2009
DOI: 10.1371/journal.pone.0004366
|View full text |Cite
|
Sign up to set email alerts
|

New Protocetid Whale from the Middle Eocene of Pakistan: Birth on Land, Precocial Development, and Sexual Dimorphism

Abstract: BackgroundProtocetidae are middle Eocene (49–37 Ma) archaeocete predators ancestral to later whales. They are found in marine sedimentary rocks, but retain four legs and were not yet fully aquatic. Protocetids have been interpreted as amphibious, feeding in the sea but returning to land to rest.Methodology/Principal FindingsTwo adult skeletons of a new 2.6 meter long protocetid, Maiacetus inuus, are described from the early middle Eocene Habib Rahi Formation of Pakistan. M. inuus differs from contemporary arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(164 citation statements)
references
References 32 publications
2
160
0
1
Order By: Relevance
“…Dorudon is a composite of UM 101215 and UM 101222 (Uhen, 2004). Maiacetus is from specimen GSP-UM 3551 (Gingerich et al, 2009). ,106.9 L11 -FIGURE 6-MUSM 1465, material belonging to Supayacetus muizoni, n. gen. n. sp.…”
Section: Supayacetus Muizoni New Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorudon is a composite of UM 101215 and UM 101222 (Uhen, 2004). Maiacetus is from specimen GSP-UM 3551 (Gingerich et al, 2009). ,106.9 L11 -FIGURE 6-MUSM 1465, material belonging to Supayacetus muizoni, n. gen. n. sp.…”
Section: Supayacetus Muizoni New Speciesmentioning
confidence: 99%
“…In addition, the recently described Maiacetus was also added as a new taxon to the matrix. Character codings for the new Peruvian taxa and Maiacetus Gingerich et al 2009 are listed in Supplemental Table 4 (online archives). In the second stage of the analysis, a stratigraphic character was added to the analysis and overall most parsimonious trees were explored in MacClade (Maddison and Maddison, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that the head motions of the ancestors of modern cetaceans might have been increased and their canal sizes decreased during their early evolution, with the small size of the canals remaining phylogenetically constrained despite the animals returning later to less agile behaviors. Given the disadvantage of small canals (Spoor et al, 2007) and the finding that a broad tail evolved with stabilizing flippers (Gingerich et al, 2009), this seems unlikely. An alternative proposed explanation is that the cetacean vestibular system has become profoundly hypofunctional to help prevent motion sickness (Ketten, 2000).…”
Section: Function Of the Semicircular Canals In Cetaceansmentioning
confidence: 99%
“…Suggested cephalic presentation in a member of Protocetidae, an Eocene family of Archeoceti, became the point for a recent discussion (Gingerich et al, 2009;Thewissen and McLellan, 2009): female remnants of Maiacetus inuus (the species described by Gingerich et al, 2009) contained the remnants of a foetus or newborn of the same species. If it was a near-term foetus, the authors concluded, it was an evidence for giving birth on land rather than in water.…”
Section: E-36mentioning
confidence: 99%